Horn of Africa: IGADMIS - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
IGADMIS, the market information system of the Intergovernmental Authority on Development (IGAD), provides crop and livestock market prices for farmers in Djibouti, Eritrea, Ethiopia, Kenya, Sudan and Uganda, in order to encourage intra-regional trade, foo